Creole… English: West Indian Writing as Translation - Akai, Joanne (TTR, 1997)
AbstractCreole... English: West Indian Writing as Translation — This paper looks at the use of language(s) in Indo-Caribbean (i.e., West Indian of East Indian descent) writings. West Indian writers are Creole, in every sense of the term: born in (former) British colonies, they have a hybrid culture and a hybrid language. They operate from within a polylectal Creole language-culture continuum which offers them a wide and varied linguistic range (Creole to Standard English) and an extended cultural base ("primitive" oral culture to anglicized written culture). Indo-Caribbean writers, however, have access, not only to the Creole language-culture continuum, but also to the pre-colonial cultural, linguistic and religious traditions of their ancestors who came from India in the 19th century. But if Creole is the mother-tongue of all West Indians, English is the only language they know to read and write. West Indian literature in English constitutes an intricately woven textile of Creole and English : a hybrid writing made possible through the translation of Creole experience into English; oral Creole culture into written English; the Creole language into the English language. In fact, West Indian literature in English can be considered self-translation, for which the presence of the author as the translator gives authority to the hybridized product, a true extract of the West Indian writer and his Caribbean language-culture.